Clinico-pathological study of odontomas in 19 Libyan patients - Mohamed S. H. Ingafou; Ali M Elmurtadi (Wolters Kluwer Medknow Publications, 2013)
Background: Odontomas are among the most common benign odontogenic tumors, which are mostly discovered in the first and second decades of life with no clear sex predilection. Materials and Methods: The present retrospective study reviews the clinical, radiological, and the histopathological characteristics of odontomas in 19 Libyan patients seen during the last 18 years in our department. Results: Most odontomas in our study were discovered when they obstruct a tooth from an eruption at its normal eruption time although a few cases were noticed on routine radiological examination of the region. Panoramic radiographs computed Tomography Scan of the area and the histopathological examination are helpful to elicit the diagnosis. Two cases in this series were found associating with dentigerous cyst and in another two cases the odontomas were seen erupting intraorally. Conclusion: Odontomas should be considered in the differential diagnosis of the mixed radioopaque radiolucent lesions, especially if they found obstructing the teeth from eruption.